Differential behavior of sugarcane (Saccharum species hybrid) genotypes towards varying concentrations of pH for rapid in vitro micropropagation - YADAV, SURESH; PATEL, V N; RAVINDRABABU, B T; REDDY, VEERASENA; NAGARAJA, T E (The Indian Journal of Agricultural Sciences, 2020)
Sugarcane (Saccharum species hybrid) is not only an important cash crop but also major source of sugar industry worldwide. An effort was made to understand the effect of varying levels of medium pH for testing differential response of sugarcane genotypes (Co 86032, Co 85004 and Co 99004) on in vitro shoot initiation, induction, multiplication and root formation. The shoot apical meristem of the three varieties was cultured on MS medium with different pH levels. Aseptic meristem cultures of the three sugarcane genotypes were cultured in vitro on the medium with five pH concentrations, viz. 4.8, 5.0, 5.4, 5.6 and 5.8. Co 85004 was found to show its response towards the medium pH at 5.6 in producing highest number of shoots (~22). However, Co 99004 responded well towards medium pH at 5.4 which produced ~21 numbers of shoots and Co 86032 exhibited its potentiality towards pH only at 5.8 levels (~17) on 180 days after inoculation. The response of all the genotypes were on par towards pH 7.0 which produced highest number of roots. At pH 5.8 genotype, Co 86032 produced highest shoot length (~3 cm) followed by Co 85004 (~2 cm) and Co 99004 (~2 cm). The study revealed that medium adjusted with pH 4.8, pH 5.8 and pH 7.0 levels resulted in optimum in vitro shoot initiation, induction, multiplication and root formation responses in Co 85004, Co 99004 and Co 86032, respectively.